Удосконалення організаційної діяльності в Головному управлінні Пенсійного фонду України у Львівській області - Пилипів, Андрій Богданович; Pylypiv, Andrii Bohdanovych (Національний університет "Львівська політехніка", 2023)
Організаційна діяльність визначає ефективність функціонування структури, її здатність до адаптації до змін у середовищі та досягнення стратегічних цілей. Постійні зміни в економічних, соціальних та технологічних умовах створюють нові виклики для організацій. Дослідження організаційної діяльності допомагають зрозуміти, як організації реагують на ці зміни, як вони адаптують свої стратегії, структури та процеси, щоб залишатися конкурентоспроможними та ефективними. Крім того, організаційна діяльність має прямий вплив на якість життя співробітників, їхнє задоволення роботою та загальну продуктивність. Тому дослідження в цій галузі може сприяти покращенню умов праці, забезпеченню ефективного управління та підвищенню результативності організацій у цілому. Об’єкт дослідження – Головне управління Пенсійного фонду України у Львівській області. Предметом дослідження бакалаврської кваліфікаційної роботи є удосконалення організаційної діяльності. Метою бакалаврської кваліфікаційної роботи є дослідження удосконалення організаційної діяльності в Головному Управлінні Пенсійного фонду України у Львівській області. У першому розділі роботи здійснено огляд літературних джерел та нормативно-правової бази за проблемою удосконалення організаційної діяльності в Головному управлінні Пенсійного фонду України. Звернено особливу увагу на особливості організаційної діяльності, а також на методики удосконалення. Надалі здійснено аналізування діяльності Головному управлінні Пенсійного фонду України у Львівській області за проблемою удосконалення організаційної діяльності в Головному управлінні Пенсійного фонду . Для цього охарактеризовано діяльність організації, здійснено аналізування фінансового стану, а також проаналізовано проблеми організаційної діяльності. У межах проектного заходу запропоновано запровадження використання штучного інтелекту в удосконаленні організаційної діяльності в Головному управлінні Пенсійного фонду України у Львівській області. Реалізація даного заходу дасть змогу Головному управлінню Пенсійного фонду України у Львівській області досягти низки позитивних ефектів, що описані у роботі.

Organisational performance determines the effectiveness of the structure, its ability to adapt to changes in the environment and achieve strategic goals. Constant changes in economic, social and technological conditions create new challenges for organisations. The study of organisational performance helps to understand how organisations respond to these changes, how they adapt their strategies, structures and processes to remain competitive and effective. Furthermore, organisational performance has a direct impact on employees' quality of life, job satisfaction and overall productivity. Therefore, research in this area can contribute to improving working conditions, ensuring effective management and increasing the performance of organisations in general. The object of the study is the Main Department of the Pension Fund of Ukraine in Lviv region. The subject of the bachelor's thesis is the improvement of organisational performance. The purpose of the bachelor's thesis is to study the improvement of organisational performance in the Main Directorate of the Pension Fund of Ukraine in Lviv region. In the first chapter of the work, the author reviews the literature and the regulatory framework on the problem of improving organisational performance in the Main Department of the Pension Fund of Ukraine. Particular attention is paid to the peculiarities of organisational activities and methods of improvement. Subsequently, the article analyses the activities of the Main Department of the Pension Fund of Ukraine in Lviv region on the problem of improvement of organisational activity in the Main Department of the Pension Fund. For this purpose, the activities of the organisation were characterised, the financial situation was analysed, and the problems of organisational performance were analysed. As part of the project measure, it is proposed to introduce the use of artificial intelligence in improving organisational performance at the Main Department of the Pension Fund of Ukraine in Lviv region. The implementation of this measure will allow the Main Department of the Pension Fund of Ukraine in Lviv region to achieve a number of positive effects described in the paper.
Improvement of organizational activities in the Head Office of the Pension Fund of Ukraine in Lviv region
Keywords: 6.281.00.00; – організаційна діяльність; штучний інтелект; методики вдосконалення; удосконалення; інновації; управління; - organisational activity; artificial intelligence; improvement methods; improvement; innovation; management. List of used literature sources 1. Project and investment management. O. A. Shulga. Kyiv : CP "Komprint"; 2021. 188 с. 2. Spivak; S. M. Management of enterprise competitiveness: theory; methodology; practice : monograph by S. M. Spivak. Ternopil: Palianytsia V. A.; 2020. 404 с. 3. Bilyk; O. Budget management: a textbook. Bilyk OI; Khim M. K. Lviv: Lviv Polytechnic; 2021. 340 с. 4. Samoilenko; Inna Oleksandrivna. Management of organisations : textbook by I. O. Samoilenko ; National Aerospace University named after M. E. Zhukovsky "Kharkiv Aviation Institute". Kharkiv: KHAI; 2020. 279 с. 5. Financial management: a study guide for self-study of the discipline / ed. O. Antonova and others; National Academy of Public Administration. Kyiv: National Academy of Public Administration; 2019. 160 с